Alternative of Police Style and Police Subculture: Some Early Notes - Dedy Tabrani (Budapest International Research and Critics University, 2019)
Given the accelerated transformation of the National Police program towards an independent, professional Polri, it basically includes aspects of bureaucratic reform in the internal environment of police institutions. because bureaucratic reform involves structuring aspects related to structure, instrumental and cultural to build the legitimacy of public trust. Indeed, the procedural principle of 'frijsermessen' should be as Jimly said above, in relation to the performance of the Police from the aspect of bureaucracy in increasing police professionalism, it should be necessary to develop it in the internal environment of the police institution. Considering that the police's performance is directly in touch with the community in the process of administrative services and law enforcement.